Effect of Heat Treatment on Microstructure and Mechanical Properties of 6061 Aluminum Alloy - Ridhwan, J.; Noor, J.A.; Zakaria, M.S.; Zulfattah, Z.; Hafidzal, M.H.M. (Journal of Engineering and Technology (JET), 2014)
The objective of this study was to illustrate the effect of various cooling rate and precipitation hardening on microstructure and mechanical properties of 6061 aluminum alloy. Samples were solution treated at 400oC before cooling in furnace, air, and water quench. Precipitation hardening was conducted by solution treating samples at 530oC followed by water quench and reheating at 100oC and 200oC. It was observed that the fast cooling rate on quenched sample produced finer grain and higher strength while slow cooling rates on annealed sample produced coarser grain and lower tensile strength. Longer precipitation hardening time resulted in larger precipitates size which led to drop in strength (over aged). Meanwhile, higher temperature resulted in shorter time to reach over aging. Precipitation hardening at 100oC for seven hours had successfully increased the UTS by 95.9% to 625 MPa due to formation of finely dispersed precipitates. Meanwhile, annealing had lowered the UTS by 62% to 197 MPa due to formation of coarser grain.